Profiling the Nitrogen using YARA ALS nitrogen sensor tractor at young oil palm in share farm UiTM Jasin / Muhammad Nawab Hazim Mohd Azhan and Mohd Hudzari Razali - Mohd Azhan, Muhammad Nawab Hazim; Razali, Mohd Hudzari (Faculty of Plantation and Agrotechnology, 2018)
Nitrogen is one of the macronutrients needed by all type of plants in order for them to growth into healthy plant. Nitrogen is also one of the important elements in plants because of its role in the chlorophyll production in the leaf. Plants will grow healthy if they receive insufficient amount of nitrogen needed. The study is conducted at Share Farm UiTM Jasin, Melaka. The YARA ALS N-Sensor has been used to determine the Nitrogen needed by the young oil palm (Elaeis gitineensisj. The result of visual analysis comes in a raster map. The colour in the map represents the needed Nitrogen kg/ha for the field. The area in the map shows 6.0 % (<170 N kg/ha), 7.6% (170- 180 N kg/ha), 16.5 % (180- 190Nkg/ha), 30.1 %(19 0 -2 0 0N kg/ha), 23.0 % (200-210 N kg/ha) and 16.7 % (> 210 N kg/ha). The area with higher percentage indicates that the most area that have 190 - 200 N kg/ha meanwhile the area with less percentage indicates that the area have less than 170 N kg/ha. The recommended N kg/ha from previous study is 192 N kg/ha. Hence, the area with less than 192 N kg/ha should be applied with Nitrogen fertilizer meanwhile the area with more than recommended did not need to applied Nitrogen fertilizer but need to be monitored.